Stakeholders’ positioning in the projects’ implementation - I. M. Zaychenko; D. V. Miroshnichenko; A. O. Prokudina (Вестник университета)
Today, most people are talking about project activities and their effectiveness. Among the aspects considered in project management, there is no management of stakeholders, although their influence and participation determine the success of the project. Positioning is an important stage in project management, because it is the correct distribution of stakeholders into groups that makes it possible to build the right strategy for interacting with t stakeholders and minimize their negative impact on the project. There are several approaches to stakeholder positioning in the scientific literature, but they are not always used in practice. This decision is due to distrust of the positioning stakeholders’ process, possible mistakes in decision-making and the lack of a program to help the project manager. The article presents a way to improve the process of positioning stakeholders by creating a desktop application. Such application was developed by the authors of the article through one of the most popular programming languages Python and the well-known PyQt5 framework. As a result of using the application, the project manager receives a completed matrix where stakeholders are located on the basis of the completed information, and the opportunity to get the most out of working with stakeholders.